Integrated weed management with strategic tillage can maintain soil quality in continuous living cover systems - Devyn McPheeters; Devyn McPheeters; Mary Ann Bruns; Mary Ann Bruns; Heather D. Karsten; Curtis J. Dell (Frontiers in Sustainable Food Systems, 2022)
Maximizing living cover and minimizing soil disturbance with no-till are key strategies in regenerative row-crop production. Although living cover and no-till can increase beneficial soil carbon and water stable aggregates (WSA), annual crops in rotation with perennials often rely on herbicides to control weeds and terminate perennials. Integrated weed management (IWM) reduces reliance on herbicides by employing multiple weed control strategies including tillage and/or cultivation. However, many no-till growers are reluctant to implement some soil disturbance due to concerns about negative impacts on soil health. For that reason, we hypothesized that compared to continuous no-till and standard herbicides (NT-SH), a strategic inversion tillage in IWM (ST-IWM) would result in lower soil carbon and WSA in the year following the tillage event. We also hypothesized that soil carbon and WSA would not differ between the two systems when sampled after cover cropping and 2 years of perennials. We tested these hypotheses within a 6-year, diverse, dairy crop rotation initiated in 2010 in central Pennsylvania in a channery silt loam soil. The systems were compared in split-plots in a full crop entry experiment, where the six phases of the crop rotation were planted every year in a randomized complete block design, replicated four times. We compared the soil health indicators in spring 2010 prior to the start of the experiment and in 2013 and 2019 following inversion tillage (ST-IWM) or herbicide termination (NT-SH) of the perennial forage in the first year of the rotation. We also compared these indicators in the sixth year of the rotation after 3 years of annual and cover crops and 2 years of perennial forage. We sampled at two depths: 0–5 and 5–15 cm for total carbon and bulk density, 0–5 cm for labile carbon and 0–15 cm for WSA. Results indicate that despite initial smaller soil health values in the ST-IWM system following inversion tillage, all properties except labile carbon were similar to the NT-SH system in the sixth year of the rotation.